Students' Self-Confidence in Speaking Skill - Markus Deli Girik Allo; Arnovan Priawan (Universitas Cokroaminoto Palopo, 2019)
The objective of the research was to find out whether or not describing people improve students’ self-confidence in speaking skill by the second grade of SMK Kristen Makale. In doing this research, the writer used quantitative method. The population of this research was the second grade students which consist of 139 students and divided into eight classes. This research employs a cluster sampling where the writer took only 25 students as respondents. The instrument that used by the writer in collecting data is questionnaire. The result of this research found that describing people could improve students’ self-confidence in speaking. It was proved by the mean score of the students in questionnaire one (Q1) is 67.88 (precisely self-confidence level) and students mean score in questionnaire two (Q2) is 79.76 (medium self-confidence level). It means that the students have shown raising the self-confidence level from precisely into the medium after learning using describing people.